Allogeneic cord blood regulatory T cells decrease dsDNA antibody and improve albuminuria in systemic lupus erythematosus - Lyu, Mi-Ae; Tang, Ximing; Khoury, Joseph D.; Raso, Maria Gabriela; Huang, Meixian; Zeng, Ke; Nishimoto, Mitsutaka; Ma, Hongbing; Sadeghi, Tara; Flowers, Christopher R.; Parmar, Simrit (Frontiers in Immunology, 2023)
Background Lupus nephritis (LN) constitutes the most severe organ manifestations of systemic lupus erythematosus (SLE), where pathogenic T cells have been identified to play an essential role in ‘helping’ B cells to make autoantibodies and produce inflammatory cytokines that drive kidney injury in SLE. Regulatory T cells (Tregs), responsible for decreasing inflammation, are defective and decreased in SLE and have been associated with disease progression. We hypothesize that treatment with allogeneic, healthy Tregs derived from umbilical cord blood (UCB) may arrest such an inflammatory process and protect against kidney damage. Methods UCB-Tregs function was examined by their ability to suppress CellTrace Violet-labeled SLE peripheral blood mononuclear cells (PBMCs) or healthy donor (HD) conventional T cells (Tcons); and by inhibiting secretion of inflammatory cytokines by SLE PBMCs. Humanized SLE model was established where female Rag2-/-γc-/- mice were transplanted with 3 × 106 human SLE-PBMCs by intravenous injection on day 0, followed by single or multiple injection of UCB-Tregs to understand their impact on disease development. Mice PB was assessed weekly by flow cytometry. Phenotypic analysis of isolated cells from mouse PB, lung, spleen, liver and kidney was performed by flow cytometry. Kidney damage was assessed by quantifying urinary albumin and creatinine secretion. Systemic disease was evaluated by anti-dsDNA IgG Ab analysis as well as immunohistochemistry analysis of organs. Systemic inflammation was determined by measuring cytokine levels. Results In vitro, UCB-Tregs are able to suppress HD Tcons and pathogenic SLE-PBMCs to a similar extent. UCB-Tregs decrease secretion of several inflammatory cytokines including IFN-γ, IP-10, TNF-α, IL-6, IL-17A, and sCD40L by SLE PBMCs in a time-dependent manner, with a corresponding increase in secretion of suppressor cytokine, IL-10. In vivo, single or multiple doses of UCB-Tregs led to a decrease in CD8+ T effector cells in different organs and a decrease in circulating inflammatory cytokines. Improvement in skin inflammation and loss of hair; and resolution of CD3+, CD8+, CD20+ and Ki67+ SLE-PBMC infiltration was observed in UCB-Treg recipients with a corresponding decrease in plasma anti-double stranded DNA IgG antibody levels and improved albuminuria. Conclusions UCB-Tregs can decrease inflammatory burden in SLE, reduce auto-antibody production and resolve end organ damage especially, improve kidney function. Adoptive therapy with UCB-Tregs should be explored for treatment of lupus nephritis in the clinical setting.